SISTEM INFORMASI PELANGGARAN DAN AKADEMIK SISWA PADA SMA N 1 LUBUK BASUNG - Firdaus, Firdaus; Wahyuni, Ritna; Saputra, Ade; Pratomo, Dhanu Bagas (Universitas Halu Oleo, 2020)
Abstract — Senior High School 1 Lubuk Basung records and processes student data, grades, class data, teacher data, subject data, and violation data, as well as data reports that are still done manually using paper. Difficulties in recording and processing the large number of student grades, the number of students, and the number of students who commit violations at school results in the data obtained being less accurate. To improve data accuracy, it is necessary to build a computerized academic information system. This study uses research methods such as preliminary research, data collection, data analysis, design, implementation of programs and results as well as testing applications and the results that will be generated later. This study aims to build a web portal for academic data of schools at Lubuk Basung State High School 1. This application was developed using the type of Web with MySql Database and uses research methods in field research, library research, and laboratory research. And this Web works to be able to present information in the form of student menus, guardian teacher menus, counseling guidance teacher menus, and admin menus that are useful for processing all academic data with the web. This information system can help schools process all data more efficiently, help guardian or counseling teachers who are tasked with processing student data so that the process is faster and easier, and improve manual systems into more efficient computer systems both in terms of time and power.Keyword — Academic, Database, MySQL, UML. Abstrak — SMA Negeri 1 Lubuk Basung melakukan pencatatan dan pengolahan data siswa, nilaisiswa, data kelas, data guru, data mata pelajaran, dan data pelanggaran, serta laporan data masih dilakukan dengan manual yaitu dengan memakai kertas. Kesulitan dalam mencatat dan memproses banyaknya nilai siswa, jumlah siswa, maupun banyaknya siswa yang melakukan pelanggaran disekolah mengakibatkan data yang diperoleh menjadi kurang akurat. Untuk meningkatkan keakuratan data, diperlukan pembangunan sistem informasi akademik yang terkomputerisasi. Penelitian ini menggunakan metode penelitian seperti penelitian pendahuluan, pengumpulan data, analisa data, perancangan, implementasi terhadap program dan hasil serta pengujian aplikasi dan hasil yang nanti dihasilkan. Penelitian ini bertujuan untuk membangun web portal sebuah data akademik sekolah pada Sekolah Menengah Atas Negeri 1 Lubuk Basung. Aplikasi ini dikembangkan menggunakan tipe Web dengan Basis Data MySql dan menggunakan metode penelitian penelitian lapangan, riset perpustakaan, serta penelitian laboratorium. Dan Web ini bekerja untuk dapat menyajikan informasi berupa menu siswa, menu guru wali, menu guru bimbingan konseling, dan menu admin yang berguna untuk memproses seluruh data akademik dengan web. Sistem informasi ini dapat untuk membantu pihak sekolah dalam memproses seluruh datanya agar lebih efisien, membantu guru wali atau guru bimbingan konseling yang bertugas memproses data siswa agar proses lebih cepat dan mudah, serta memperbaiki sistem manual menjadi sistem komputer yang lebih efisien baik dari segi waktu maupun tenaga.Kata kunci — Akademik, Database, MySQL, UML.